Reading between the lines: Novel insights on wild Pacific harbour porpoise (Phocoena phocoena vomerina) social communication through narrow-band high frequency click trains. - Amy Migneault; Karina Dracott; Nick Tregenza; Chloe V Robinson (PLoS ONE)
For cetaceans that produce narrow-band high-frequency click trains such as the Pacific harbour porpoise (Phocoena phocoena vomerinae), social acoustic behavior is poorly understood. While harbour porpoises have a reputation of being generally non-social and often solitary, few studies have aimed to quantify acoustic social communication for this species. In the waters surrounding the Port of Prince Rupert in British Columbia, Canada, harbour porpoises are often seen in groups where they have been observed attempting mating and surface-active behaviors. To assess the extent of social communication amongst porpoises in this region, we analyzed a long-term passive acoustic monitoring F-POD dataset collected from two sites, coupled with a detailed social acoustic criterion for detecting patterns of non-foraging click trains. Based on these criteria, porpoises were found to be producing patterns of obvious, discrete, and repetitive click trains that were marked as social. Generalized additive models were used to identify significant temporal trends in the dataset. On average, 5.3% of click trains produced by porpoises were social. Monthly and diurnal fluctuations in social detection positive minutes (DPM) followed a similar trajectory to non-social DPM, with peak activity observed during periods of darkness and from spring to early summer with a smaller increase in the fall. At one site, 11.1% of the DPM in May were classified as social. In general, proportionally more social DPM were found during periods of more overall DPM, suggesting that porpoises were socially communicating while in proximity to one another. Notably, overall DPM significantly decreased by 53.7% over three years. This novel methodology can be replicated in other regions to gain further insight into the social acoustic behavior of harbour porpoises.